2009
DOI: 10.1002/cncr.24196
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous thermal ablation of medium and large hepatocellular carcinoma

Abstract: Knowledge about the triglyceride (fat) 1H spectrum enables quantitative determination of several triglyceride characteristics. This work describes a model‐based chemical shift imaging method that separates water and fat signal and provides maps of three triglyceride quantities: fatty acid carbon chain length, unsaturation degree, and polyunsaturation degree. The method was validated by imaging a phantom containing 10 different oils using 1.5 and 3.0 T clinical scanners, with gas–liquid chromatography as refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(58 citation statements)
references
References 64 publications
3
52
1
1
Order By: Relevance
“…The complete ablation rate was 93% for tumors measuring 4 cm or less and 38.5% for tumors larger than 4 cm, and the authors concluded that laparoscopic MWA is preferable for tumors of 4 cm or smaller. Yin XY et al (2009) reported using MWA or PRFA to treat 109 HCC patients with at least 1 tumor measuring between 3.0 cm and 7.0 cm. CA rate was 92.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The complete ablation rate was 93% for tumors measuring 4 cm or less and 38.5% for tumors larger than 4 cm, and the authors concluded that laparoscopic MWA is preferable for tumors of 4 cm or smaller. Yin XY et al (2009) reported using MWA or PRFA to treat 109 HCC patients with at least 1 tumor measuring between 3.0 cm and 7.0 cm. CA rate was 92.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The CA rate was 93% for tumors measuring 4 cm or less and 38.5% for tumors larger than 4 cm, and the authors concluded that laparoscopic MWA was preferable for tumors of 4 cm or smaller. Yin et al (2009) reported using MWA or PRFA to treat 109 HCC patients with at least one tumor measuring between 3.0 and 7.0 cm. The CA rate was 92.6%; LR occurred in 22% patients, with a median time to LR of 4.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, a trend favoring RFA was recognized in that study with respect to local recurrence and complication rates [62] . In another study by Yin et al [63] comparing the therapeutic efficacy of RFA and MWA in treating HCCs > 3 cm, both RFA and MWA were found to be effective and safe. Several studies have evaluated the efficacy of MWA when used alone in treating HCCs [63] .…”
Section: Figure 2 Axial Computed Tomography Images Before and After Rmentioning
confidence: 95%
“…In another study by Yin et al [63] comparing the therapeutic efficacy of RFA and MWA in treating HCCs > 3 cm, both RFA and MWA were found to be effective and safe. Several studies have evaluated the efficacy of MWA when used alone in treating HCCs [63] . Sato et al [64] , in one of the earliest studies, demonstrated the safety and efficacy of MWA in 19 patients with unresectable HCCs.…”
Section: Figure 2 Axial Computed Tomography Images Before and After Rmentioning
confidence: 95%